Gut Microbiome Alterations Affect Glioma Development and Foxp3 Expression in Tumor Microenvironment in Mice - Fan, Yiqi; Su, Qing; Chen, Junxiao; Wang, Yong; He, Shuai (Frontiers in Oncology, 2022)
Glioma is the most common malignant tumor of the central nervous system (CNS), with high degree of malignancy and poor prognosis. Gut microbiome (GM) is composed of microorganisms with different properties and functions, which play an important role in human physiology and biological activities. It has been proved that GM can affect the development of glioma through natural immunity, but whether GM can affect glioma through adaptive immunity and whether there are some microorganisms in the GM may affect glioma growth still remains unclear. In our study, we evaluated the relationship between GM and glioma. We proved that (Ⅰ) glioma growth can induce structural changes of mice GM, including the decreased abundance of Bacteroidia and increased abundance of Firmicutes. (Ⅱ) GM dysbiosis can down-regulate Foxp3 expression in brain and promote glioma growth. Balanced environment of GM can up-regulate the expression of Foxp3 in brain and delay the development of glioma. (Ⅲ) Bacteroidia, which increased abundance is associated with accelerated glioma progression, while decreased abundance is associated with delayed glioma progression, may be one of the key microorganisms affecting glioma growth. This study is helpful to reveal the relationship between GM and glioma development and provide new ideas for adjuvant therapy of glioma.